Determinants of Overweight Among Female Health Workers At Community Health Centers in Aceh Tenggara Regency - Mira Maharani; Etti Sudaryati; Zulhaida Lubis (International Journal of Health and Medicine, 2026)
Overweight is a growing global health concern, especially among female healthcare workers who are expected to serve as community role models. In Indonesia, adult obesity prevalence reached 23.4% in the 2023 SKI Survey, while Aceh recorded an increase from 24.4% in 2018 to 34.3% in 2023. This study aimed to analyze determinants of overweight among female healthcare workers at community health centers in Southeast Aceh Regency. The study was conducted from July to December 2025 using a cross-sectional design involving 191 respondents selected through cluster random sampling. Overweight status was measured anthropometrically, nutrient intake using the SQ-FFQ, physical activity through a 24-hour recall questionnaire, and sleep disturbances using the SSDA. Data were analyzed using chi-square and multiple logistic regression at α=0.05. Bivariate analysis showed significant associations between overweight and energy intake, protein intake, fat intake, physical activity, and sleep disturbances. Multivariate analysis identified physical activity as the dominant factor. Female healthcare workers with higher energy intake and low physical activity had a 98% probability of being overweight. Therefore, regular exercise and balanced nutritional intake are recommended to reduce overweight risk.